Barriers to achieving asthma control in adults: evidence for the role of tiotropium in current management strategies - Jenkins C (Dove Medical Press, 2019)
Christine Jenkins Department of Thoracic Medicine, The George Institute for Global Health and Concord Clinical School, University of Sydney, Sydney, NSW, Australia Abstract: Despite the availability of a range of treatment options and management guidelines, a high proportion of adults with asthma remain uncontrolled. The challenge of managing uncontrolled asthma includes providing efficacious treatment while limiting side effects, recognizing situations when a change in asthma therapy is required, and considering patient preferences and satisfaction. In line with the Global Initiative for Asthma report, asthma management is based on a backbone of inhaled corticosteroid (ICS) therapy and use of add-on therapies to achieve disease control. This review considers whether add-on options could be better utilized in clinical practice. A number of long-acting muscarinic antagonists are in development, but tiotropium is the most widely studied for use in asthma. Evidence demonstrating the efficacy of tiotropium as an add-on therapy to at least ICS in adults with symptomatic mild, moderate, and severe asthma is presented from randomized controlled trials and real-world evidence. In addition, the benefit of tiotropium therapy in a wide range of patient phenotypes and disease severities without the need for biomarker assessment is discussed. Additional strategies that complement this approach, such as recognizing and overcoming barriers to adherence, ensuring optimal device use, and education and support to enhance patient–physician communication, are discussed. Physician education can also help raise awareness that additional management options are available for patients with moderate-to-severe asthma who remain uncontrolled on ICS/long-acting β2-agonist treatment. Keywords: asthma, long-acting muscarinic antagonists, tiotropium, adults